Atypical presentation of a fish bone foreign body: A case report and review of the literature - Bagdadi, Rabab R; Baghdadi, Leena R (Global Journal of Medical and Clinical Case Reports, 2021)
Introduction: Fish bone Foreign Body (FFB) accidental ingestion is a most common presenting complaint for patients attending the emergency department. It is more frequently lodged within the oropharynx and the oesophagus. However, fish bone impacting in the respiratory system is extremely rare; accounting for 14% of reported cases, with approximately few cases reported in the literature involved the lower airway. Patient concern: A 27- year-old man presented clinically as a case of chest infection with a 5-day history of palpitation, right pleuritic chest pain and shortness of breath. Diagnosis: We report a case of atypical presentation of FFB ingestion. Although patients with foreign bodies’ ingestion sometimes presented with cough, there are a wide spectrum of clinical symptoms, especially those with lower airway FFB; where imaging findings are not usually spotted in the emergency department to point to the diagnosis. Intervention: Swab for COVID-19 was negative and the initial chest X-ray showed poor inspiratory effort and no air space opacity. Although CT pulmonary angiography for pulmonary embolism was negative, an incidental finding suggestive of foreign body was reported in the right lower lung region. Outcomes: The foreign body was distal within the lung parenchyma; therefore, there was no need for urgent surgical intervention and there should be a 1-month outpatient clinic follow-up and patient was discharged on antibiotic. Conclusion: Although fish bone ingestion is a common food related foreign body ingestion, cases can often present a diagnostic dilemma and can be easily misdiagnosed or mistaken for other diagnoses. Therefore, vigilant and thorough history taking, and the consideration of a FFB in the differential diagnosis is essential.